Medan Youth and Community Center - Samsul Bahri; Harun Arrasyid Sitorus (Talenta Publisher, 2018)
Medan City is one of the big cities in Indonesia that also can not be separated from the process of guidance and talent of the youth who often become issues that are closely linked with the nation's moral problems as a whole there is no guidance and talent for young people. At the regional level, the number of youths reaches 40% of the total population. It is the responsibility of the government to provide a means of talent development to boost the sporting achievements and youth work that will become leaders in the future. Based on the background of this problem required a facility that can support and develop the talent of the youths in the city of Medan.